2010
DOI: 10.1111/j.1467-9221.2010.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Logic of Collective Action: Partisans Cooperate and Punish More Than Nonpartisans

Abstract: Laboratory experiments indicate that many people willingly contribute to public goods and punish free riders at a personal cost. We hypothesize that these individuals, called strong reciprocators, allow political parties to overcome collective action problems, thereby allowing those organizations to compete for scarce resources and to produce public goods for like-minded individuals. Using a series of laboratory games, we examine whether partisans contribute to public goods and punish free riders at a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Clearly, party identification helps individuals overcome the disincentive to participate. In fact, party identification increases cooperation in collective action games and even boosts willingness to pay a personal cost to punish free riders (Smirnov, Dawes, Fowler, Johnson, & McElreath, ). But what is it about party identification that makes people think and act this way?…”
Section: Identity Emotion and Cooperationmentioning
confidence: 99%
“…Clearly, party identification helps individuals overcome the disincentive to participate. In fact, party identification increases cooperation in collective action games and even boosts willingness to pay a personal cost to punish free riders (Smirnov, Dawes, Fowler, Johnson, & McElreath, ). But what is it about party identification that makes people think and act this way?…”
Section: Identity Emotion and Cooperationmentioning
confidence: 99%
“…Biologically-informed studies have tested predictions related to the idea that modern humans' representations of political parties are shaped by a psychology of coalitional alliances: decreasing testosterone levels (a correlate of status loss) is observed among individuals who vote for a loosing political party (Apicella & Cesarini, 2011;Stanton et al, 2009), partisanship plays a significant role in assortative mating today (as more classical group identities such as religion and race also do) (Alford et al, 2011), and partisans have been found to be more likely to contribute to public goods and punish in economic games (a correlate of a disposition to engage in collective action; Smirnov et al, 2010). Importantly, for the purpose of the present study, these past studies assume that political affiliations are cognitively represented as alliances and test predictions that only indirectly bear on this claim.…”
Section: The Psychology Of Politicsmentioning
confidence: 99%
“…In conditions without punishment, participants contributed, on average, 3.7 units of a 20-point endowment (18.5%) to the public good, whereas they contributed an average of 11.5 points of their 20point endowment (57.5%) in conditions involving punishment-a 39-percentage-point increase. Subsequent research has explained how decentralized altruistic punishment figures centrally in humanity's large-scale cooperation (Bowles & Gintis, 2011;Fischbacher & Fehr, 2003) and appears prevalent among individuals who participate in collective endeavors that exhibit the social dilemma's incentive structure (Smirnov, Dawes, Fowler, Johnson, & McElreath, 2010). The role of decentralized costly punishment in addressing the social dilemmas involved in the COVID-19 response, however, warrants careful consideration.…”
Section: Bolstering Mandatory Cooperative Measures Via Altruistic Punmentioning
confidence: 99%